Comorbid of Obsessive-Compulsive Disorder and Schizophrenia: A Case Report - Budi Pratiti; Jimmi Aritonang (Scientia Psychiatrica, 2020)
Introduction: Schizophrenia was a chronic mental disorder that is marked by abnormal social and impairment in reality testing ability. A person diagnosed with schizophrenia may experience a number of symptoms including hallucinations, delusions, disorganized thinking, bizarre speech, and behavior. Obsessive-compulsive disorder is well known as a comorbid of schizophrenia. Comorbid OCD will affect the treatment of schizophrenia and other mental disorder. Case presentation: A 14-year-old student Muslim boy from a rural household in Central Java, Indonesia who had 8 years of formal education and live with his parent was brought to the emergency department of a mental hospital by his parents who reported a one-year history of excessive washing of his body, soaking his body for hours in the bathtub and sleep in the bathroom. The patient first fell in January 2019; over a six-month period, he became progressively deteriorated, lost interest in his hobby, stopped going to school, and reduced his food intake. After one week treatment of with venlafaxine and risperidone, He became more cooperative and interactive with the examiner. At that time, the patient reported delusional beliefs about contamination and paranoid delusion, and there were several indications of formal thought disorder, including derailment, neologisms, concrete thinking, circumstantiality, and illogicality. An intelligence test revealed average intelligence (IQ=100). The total score of the Brief Psychiatric Rating Scale (BPRS) 3 dropped from 42 to 24, the score on the Yates-Brown Obsessive-Compulsive Symptoms (YBOCS)4 scale dropped from 24 to 18, and the score on the Global Assessment of Functioning scale (GAF)5 increased from 25 to 55. After discharge, the patient adhered to his medication regimen, and three months after discharge, his clinical improvement persisted; he was able to maintain his personal hygiene and take care of his daily needs, but he remained socially isolated and was unable to return to school. Conclusion: Obsessive-compulsive disorder and schizophrenia could happen together in one individual. The treatment should consider the underlying condition and cognitive function, especially if the patient is of productive age.